PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 001 SEI KIJANG - Lusiana, Ade; Alim, Jesi Alexander; Syahrifuddin, Syahrifuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This was a classroom research (PTK) which has two cycles which was conducted on May 2015. The data shown the either learning process increased. The basic score of daily examination as 9,5% which 12 students passed and 8 students failed. The ending of daily examination was 60% and the average was 67,5 on the passing grade. The second daily examination also increased from basic score as 14,7% which 15 students passed and 5 students failed. The ending of second daily examination was 75% and the average was 82,2. Based on the explanation above it can be concluded that the implementation of quantum teaching increased students’ achievement the result of mathematics studies of students III grade of State Elementary School 001 Sei Kijang.Keywords : Quantum Teaching, Students Achievement The Result Of Mathematics Studies